Evaluation of the e-health literacy levels and related factors in vocational school of health services students - Genç, Ezgi; Genç, Tuncay; Gunes, Gulsen (My University, 2024)
Aim: This study evaluated the e-health literacy levels and related factors in Vocational School of Health Services students. Methods: It is a cross-sectional study conducted between January and February 2019 on 778 students studying at the Vocational School of Health Services in Elazig. The research data were collected using the “Personal Data Form”, and “e-Health Literacy Scale (eHEALS)”. The data were evaluated in the Statistical Package for the Social Sciences (SPSS) 22.0 program, with p<0.05 statistical significance. t-test, Pearson correlation analysis, one-way analysis of variance (ANOVA) and least significant difference (LSD) test were used for statistical analysis. Results: The mean age of the students was 20.4±2.6, and 66.6% were women. The eHEALS score of the participants was 28.7±6.92. eHEALS scores were high in women, those with more monthly income, and those who lived in the city before the university (p<0.05). There was a negative correlation between the total number of participants in the family, body height, weight, and eHEALS scores, and a positive low-level correlation between monthly income and eHEALS scores (p<0.05). Conclusion: It is important to have a high level of e-health literacy for the students who will be the health personnel of the future to fulfill their roles. It can be suggested that e-health literacy be included in the university curriculum.
Keywords: Health personnel; Health literacy; student health service